Sacubitril-valsartan for the treatment of hypertension in China: A cost-utility analysis based on meta-analysis of randomized controlled trials - Lou, Yake; Yu, Ying; Liu, Jinxing; Huang, Jing (Frontiers in Public Health, 2022)
Background: Sacubitril-valsartan was recommended in heart failure (HF) and proven cost-effective in HF. Recently, sacubitril-valsartan has been recommended to treat hypertension in Chinese expert consensus. The cost-utility of sacubitril-valsartan for hypertension remains uninvestigated. Methods: A meta-analysis of randomized controlled trials was performed to investigate the real efficacy of sacubitril-valsartan on blood pressure, compared with angiotensin receptor blockers or placebo. A lifetime Markov model was developed to compare the cost-utility of sacubitril-valsartan versus valsartan. The primary outcome was incremental costs utility ratio (ICUR), representing the ratio of incremental costs to incremental utility. The willingness-to-pay (WTP) threshold was 3 times of per capita GDP in China in 2021. Sacubitril-valsartan was considered cost-effective if the ICUR obtained was lower than the WTP threshold, and not cost-effective if higher than the threshold. Results: A total of 10 RCTs of 5,781 patients were included in the meta-analysis. For comparison of sacubitril-valsartan 400 mg/day versus valsartan 320 mg/day, a reduction in BP of -5.97 [-6.38, -5.56] (p＜0.01) was observed. Cost-utility analysis showed that for a 60 years old hypertension patient, if sacubitril-valsartan was prescribed as the antihypertensive agent, he had a life expectancy of 11.91 quality-adjusted life-years (QALY) with costs of 65,066 CNY, and if valsartan was prescribed as the antihypertensive agent, the life expectancy would be 11.82 QALY with costs of 54,769 CNY, thus an ICUR of 108,622 CNY/QALY was obtained, lower than the WTP threshold. Conclusion: Compared with valsartan, sacubitril-valsartan is more effective in reducing blood pressure and may results in more quality adjusted life year, although with higher costs. Sacubitril-valsartan is cost-effective for hypertension in current China setting under the willingness-to-pay threshold of 3 times of per capita GDP.